(untitled) (Global Journal of Human-Social Science, 2019)
The world is now experiencing a boom time of global capitalism that entirely is rooted in large-scale investments worldwide The word capital however is no more confined to the material or monetary category instead it has started analyzing cultural as well as social realities to find out new forms of profit-making investment sources Interestingly capitalism is nowadays devoted to dig out human interests and to present commodities according to those desires To understand this matter more clearly here few contents from YouTube are going to be analyzed to show how social scopophilia a pleasure principle has been targeted as a space for investment These contents are uploads of some women who share their daily life with the world around on which this study has launched a thorough qualitative analysis In order to find an answer to the question why the selected YouTubers have made their everyday life public and on the other hand why viewers get interested in others life this study has mainly focused on commodity culture of contemporary world that resultantly has brought into view how everything irrespective of their materiality and immateriality gets commodified To conclude the most determining factor behind the commodification of everyday domestic life has been a sort of scopophiliac consumerism that this particular study has earnestly attempted to establish